Site Characterization of Alluvial Silty Sand Soils by Dynamic In-Situ and Laboratory Tests - Ramazan Borujerdi, Ali (International Journal of Sustainable Construction Engineering and Technology, 2023)
Soil is normally heterogeneous and non-uniform material since it is made up of diverse types of matter. Understanding of soil parameters is one of the foremost complex assignments in geotechnical design. A few laboratory tests of soil need to carry out for engineering practices. Research facility tests take too much time to achieve and are excessive moreover. There's another elective way to urge soil parameters direct from the soil field investigation report to spare time and fetched. The objective of this consideration is to explore the relationships of soil parameters with the most commonly utilized soil investigating apparatuses SPT and CPT and other soil parameters that relate to direct applications in designing practice. In this investigate, four sets of in-situ tests were created in order to study the appropriateness of different existing CPT-SPT relationships to the alluvial silty sand soils. The recouped tests from SPT tests contain a calculable sum of fines (fc) extending from 3.5 to 39.2 percent and mean grain measure (D50) extending from 0.09 to 0.23 mm. Ponder comes about demonstrated that qc/N ratio as a function of D50 and fc-based relationships are ineffectively pertinent to the silty sand soils. This paper recommends that q/(N1)60 ratio as a function of increasing steadily can be way better related in silty sand soils rather than research facility-based D50 or fc relationships. An exertion has moreover been made to perform a comparative investigation for the compelling point of inside contact gotten from CPT, SPT, direct shear tests, and triaxial tests.